Subclinical mastitis among lactating buffaloes in the middle of Nile delta of Egypt - Zommara, Mohsen A.; El-Baz, Azza M.; El-Sherbieni, Mohamad A.; Youssef, M. M. (2008)
The incidence of subclinical mastitis among 175 lactating buffaloes was studied in three governmental buffalo fanns located in the middle of Nile delta of Egypt. Individual quarter's milk samples (699) was randomly collected and investigated for CMT, SCC, conductivity, chemical composition and mastitis causing microorganisms. The CMT positive quarters represented 21.6% of the total investigated quarters however; the front quarters were less susceptible (44.2%) to mastitis than the rear ones (55.8%). The mastitic milk resulted in a dramatic increase of SCC (19.3 x 10p5(B) compared to the normal one (1.0 x 10p5(B) with higher SCC in the left front and rear udder quarters (23.9 and 18.3%) than the right one (7.8 and 13.1 %), respectively.s
Includes references.
Summary in Arabic.
1
Keywords: Buffaloes -- Diseases; Mastitis